Interoperability update dynamic ethernet services via intelligent optical networks. - Jones, James D. (IEEE Communications magazine)
This article describes the 2005 Worldwide Interoperability Demonstration held by the Optical Internetworking Forum and showcased during SUPERCOMM 2005, The event highlighted Ethernet services transported over intelligent optical networks, using equipment from 13 of the industry's leading vendors located in seven carrier laboratory facilities around the world. The demonstration utilized a distributed optical control plane based on OIF Implementation Agreements to control a multilayer network providing Ethernet over SONET/SDH adaptation and transport. The article describes the global test network, services, architecture, and overall test approach. It also describes innovations made to the optical control plane to handle multilayer signaling and lists further refinements needed to make these services operational.